TOXICITY, ANTICANCER AND ANTIOXIDANT ACTIVITY OF EXTRACTS FROM MARINE BACTERIA ASSOCIATED WITH SPONGE Jaspis sp. - ANNISA WULAN AGUS UTAMI,; ARIS TRI WAHYUDI,; IRMANIDA BATUBARA, (International Journal of Pharma and Bio Sciences, 2014)
Sponges associated with microorganism can produce bioactive compounds such as antioxidant and anticancer. The aim of this study determines the toxicity, anticancer and antioxidant potency of marine bacteria which associated with sponges Jaspis sp. The bioactive compounds were extracted with ethyl acetate. The toxicity of extract was analyzed trough by brine shrimp lethality test (BSLT), while anticancer activity againts HeLa cell was analyzed by MTT assay and antioxidant capacity was analyzed by cupric ion reducing antioxidant capacity (CUPRAC) assay. The result showed that extract consisted of flavonoid, alkaloid, and triterpenoid which were potential as an antioxidant and anticancer. The extract had a toxic effect with the range LC50 value was 251.18 to 390.50 µg/mL. The extract could inhibited HeLa cell in the range IC50 value was 242.54 to 267.03 µg/mL. Antioxidant capacity of extract were ranged from 156.94 to 649.92 µmol trolox/g extract.